Novel route for fabrication of ZnO nanorods-Au nanoparticles hybrids directly supported on substrate and their application as gas sensors - Gasparotto, Gisane; Da Silva, Ranilson Angelo [UNESP]; Zaghete, Maria Aparecida [UNESP]; Longo, Elson [UNESP]; Perazolli, Leinig Antonio [UNESP]; Mazon, Talita (My University, 2018)
The aim of this study was to develop a novel, simple and fast route to prepare ZnO nanorods (NRs) -Au nanoparticles (NPs) hybrids directly supported on a substrate to be used in gas sensor devices. The ZnO NRs were promptly grown on interdigitated Au electrodes Al2O3 substrates by chemical bath deposition at a low temperature. After that, Au NPs were deposited by sputtering. Results obtained by XRD, SEM, EDX and TEM showed the perpendicularly aligned growth of the ZnO NRs with a hexagonal base on the substrate and the Au NPs homogeneously covered the ZnO NRs surface. The ZnO NRs-Au NPs hybrids-based sensor exhibited an improved sensor response for H2 and O2 gases compared to the ZnO NRs at 300 ºC. Due to the ability to prepare homogeneous hybrids with high surface directly supported on the substrate; the developed route might provide a convenient approach to preparing gas sensor devices.
Keywords: Chemical synthesis; Hybrids; Sensor; ZnO